Vegetation and environmental heterogeneity relationships in a Neotropical swamp forest in southeastern Brazil (Itirapina, SP) - Teixeira, Aloysio de Padua [UNESP]; Assis, Marco Antonio [UNESP]; Luize, Bruno Garcia (Elsevier B.V., 2011)
Patterns in substrate, canopy openness, tree species composition and structure were studied in a swamp forest in southeastern Brazil (Itirapina, SP), using a fine spatial scale (similar to 0.05 km(2)). Sixty quadrats of 10 m x 10 m were divided into three sample plots, located in the centre and at both ends of the forest remnant (upstream and downstream), encompassing different environmental conditions. In each quadrat we quantified and identified individuals with CBH (circumference at breast height) >= 10 cm, the chemical properties of the soil, the drainage (flooded area) and the percentage of canopy openness. We keep 5124 individuals distributed over 37 species and 25 families. The downstream site presented a lower frequency of flooding, canopy openness, species richness (15 species) and density of individuals. In the central site we found different patterns of drainage and light incidence, the greatest species richness (31 species) and density of individuals, but smaller trees both in height and in diameter. The upstream site was subject to higher frequency of flooding, with intermediate values for density and species richness (27 species). Floristic and structural variation between and within sites reflects the different environmental conditions related to substrate and canopy openness. However, a larger number of species were correlated with drainage pattern (21 species) rather than with canopy openness (14 species), suggesting that the main factor responsible for the spatial organization of the plant community in swamp forests is soil drainage. (C) 2010 Published by Elsevier B.V.
Keywords: Canopy openness; Drainage pattern; Environmental heterogeneity; Flooding; Riverine forest; Species diversity